2011
DOI: 10.1186/1687-9856-2011-10
|View full text |Cite
|
Sign up to set email alerts
|

Children with disorders of sex development: A qualitative study of early parental experience

Abstract: BackgroundClinical research on psychological aspects of disorders of sex development (DSD) has focused on psychosexual differentiation with relatively little attention directed toward parents' experiences of early clinical management and their influence on patient and family psychosocial adaptation.ObjectivesTo characterize parental experiences in the early clinical care of children born with DSD.Study DesignContent analysis of interviews with parents (n = 41) of 28 children, newborn to 6 years, with DSD.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 50 publications
(58 reference statements)
1
115
0
3
Order By: Relevance
“…In some cohorts, adults' dissatisfaction with their early surgery is high [57], while others report more positive long-term outcomes [58,59]. Parental awareness of management options and consequences of decision making due to inadequate information are important topics [60]. …”
Section: Advancing and Evidencing Psychosocial And Psychosexual Well-mentioning
confidence: 99%
“…In some cohorts, adults' dissatisfaction with their early surgery is high [57], while others report more positive long-term outcomes [58,59]. Parental awareness of management options and consequences of decision making due to inadequate information are important topics [60]. …”
Section: Advancing and Evidencing Psychosocial And Psychosexual Well-mentioning
confidence: 99%
“…'Coming to terms' may require sustained support for coping with losses and fears and for examining taken-forgranted beliefs about 'normal sexuality' and 'normal life' (Liao, 2003). Crissman et al (2011) interviewed 41 parents of children with mixed DSD diagnoses and identified a 'discordance between scientific and parental understandings of the determinants of "sex" and "gender"'. Continued exploration of these complex topics, if uncomfortable and uncertain, may require high level consultation skills and a robust therapeutic alliance.…”
Section: Engaging Parents In Dilemmatic Conversationsmentioning
confidence: 99%
“…Cinsiyeti ve cinsel kimliği belirleyecek, ancak çocuk üzerinde kalıcı değişikliklere neden olacak bu tür ameliyatlar için ailelerin onam vermesi, özellikle gelişmiş ülkelerde tartışma konusudur (14)(15)(16) . Günü-müzde, bu tür ameliyatlar için erken cerrahi yerine, çocuğun onam verebilecek yaşa kadar beklenmesini öneren görüşler giderek kabul görmektedir (17) .…”
Section: Cinsel Gelişim Sorunlarının Cerrahi Tedavisinde Etik Ve Yasaunclassified